How Accurately Do Engineers Predict Software Maintenance Tasks? - Hatton, Les (Computer (00189162), 2007)
The article discusses a case study that was performed in order to determine how well software engineers predict the type of maintenance necessary and the duration period needed for the maintenance. The types of maintenance were broken into three categories, Adaptive, Corrective, and Perfective. Time spent among these categories varies widely partly because many activities are difficult to classify and the initial appraisal of maintenance necessary is often inaccurate. This case study confirms earlier research showing considerable overlap among perfective, corrective, and adaptive maintenance tasks in software development projects. Several charts are included.